2011
DOI: 10.4103/1463-1741.82965
|View full text |Cite
|
Sign up to set email alerts
|

The influence of military service on auditory health and the efficacy of a hearing conservation program

Abstract: The influence of military service on self-assessed hearing symptoms and measured auditory function was studied as well as the efficacy of the Hearing Conservation Program (HCP) of the Swedish Armed Forces. 839 conscripts were recruited for the study at reporting to military service. They were all exposed to noise over the risk-limits from weapons and vehicles and used earmuffs and/or earplugs. Questionnaires and pure tone screening audiometry were studied at the start and the end of the military service. Retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…There are many examples of studies which have examined audiometric results in an attempt to determine the effectiveness of HCPs, including studies of longitudinal data across one (Savell & Toothman, 1987; Brink et al, 2002) or multiple (Lee-Feldstein, 1993; Dement et al, 2005) facilities within the same industry or military occupations (Wolgemuth et al, 1995; Muhr & Rosenhall, 2011)Several studies that have utilized audiometric results to analyze HCP effectiveness have found that audiometric test results do not align well with categorized noise exposures (e.g., “high” vs “low”) (Bohnker et al, 2002). Only a few studies have also evaluated quantitative noise exposures with regards to HCP performance (Savell & Toothman, 1987; Lee-Feldstein, 1993; Davies et al, 2008), and some have determined that categorized exposures are more useful than continuous quantitative estimates (Heyer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are many examples of studies which have examined audiometric results in an attempt to determine the effectiveness of HCPs, including studies of longitudinal data across one (Savell & Toothman, 1987; Brink et al, 2002) or multiple (Lee-Feldstein, 1993; Dement et al, 2005) facilities within the same industry or military occupations (Wolgemuth et al, 1995; Muhr & Rosenhall, 2011)Several studies that have utilized audiometric results to analyze HCP effectiveness have found that audiometric test results do not align well with categorized noise exposures (e.g., “high” vs “low”) (Bohnker et al, 2002). Only a few studies have also evaluated quantitative noise exposures with regards to HCP performance (Savell & Toothman, 1987; Lee-Feldstein, 1993; Davies et al, 2008), and some have determined that categorized exposures are more useful than continuous quantitative estimates (Heyer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…An elevation in the prevalence values of tinnitus, sensitivity to noise and hearing impairment was seen at release compared to before joining military service. 16 In our study only 5 cadets reported with hearing loss immediately following exposure to loud noise after firing practice. Audiometry revealed a mild deterioration of hearing in the frequencies between 3-6 kHz.…”
Section: Discussionmentioning
confidence: 80%
“…[29] Like in other series, AAT presented most often as unilateral involvement and was usually accompanied by tinnitus and hearing loss. [1330] As reported in the literature, tinnitus is almost constant and is sometimes the only symptom. [3] When tinnitus persists, it can be very disabling both psychologically (anxiety, depression) and operationally, because it may mask sound messages and cause tiredness, thereby linked to the need for greater concentration.…”
Section: Discussionmentioning
confidence: 99%